แนวทางในการพัฒนาการอุดมศึกษาของไทยตามหลักการประกันคุณภาพการศึกษาระดับอุดมศึกษา - พระธีรวัฒน์ อั้นเต้ง (มูลนิธิการจัดการเชิงพุทธ, 2022)
This article has studied the guidelines of higher education development in Thailand according to the higher education quality assurance which the education had the main issues to present as follows: 1. The necessity and objectives of higher education quality assurance. 2. The framework of the 15-year Long-Term Higher Education Plan No. 3 (2017 - 2031). 3. Higher Education Development Plan No. 12 (2017 - 2021). 4. Quality of Thai higher education. 5. Guidelines for the development of higher education in Thailand. The results showed that guidelines for the development of higher education in Thailand in accordance with the important principles of higher education quality assurance. Higher education institutions need to offer courses to meet the needs of the current and future labor market. Build a network of cooperation with agencies within higher education institutions and other higher education institutions to strengthen strengths and exchange new knowledge. Educational institutions must aim to provide in-depth specialized education to gain expertise. This is to develop quality higher education by creating new knowledge and innovations to be able to compete with other leading higher education institutions should utilize information technology to build competitiveness. and continually improve the quality of teaching and learning.